Accuracy of Mcmurry’s Test in Diagnosis Meniscal Tears - Ahmad Zeb, Farmanullah Khan, Akhtar Husain, Muhammad Shoaib Khan, Shehryar Khan, Khalid Iqbal, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Meniscal tears in knee joint are of utmost importance to be treated as these injuries not only hamper the quality of life but also lead to unrepeatable degenerative changes in the menisci which ultimately result in knee arthritis. Early diagnosis and treatment is necessary to avoid long term complications of these injuries. Certain clinical tests including McMurry’s test along with MRI knee joint aid in the diagnosis of these injuries but currently arthroscopic examination is the gold standard. Method: This prospective, cross-sectional was conducted in the department of Orthopedics, Khyber Teaching Hospital, Peshawar from Jan, 2020 to Dec, 2021, including 162 patients with suspected meniscal knee injuries. All the patient were evaluated by McMurry’s test followed by arthroscopy of the affected knee joint for diagnosis of meniscal tears. Result: Among 162 patients, 110 (67.90%) were males and 52 (32.10%) were females. The age ranged from 15 to 50 years. Most of the patients (105, 64.81%) were below 30 years of age. The mean age was 30.55±8.13 years. McMurray’s test was having sensitivity of 56.8% and specificity of 78.66% for medial meniscal tears while it had sensitivity of 67.70% and specificity of 86.33% for lateral meniscus tears. Conclusion: McMurray’s test is beneficial if used for the screening purpose for meniscal knee injuries.